Pengaruh Sistem Administrasi Perkantoran Terhadap Efisiensi Kerja Pegawai di Kantor Dinas Kesehatan Provinsi Gorontalo - Putri Dika Astuti; Melizubaida Mahmud; Agil Bahsoan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research aims to determine how much influence the office administration system has on employce work efficiency at the Gorontalo Provincial Health Office. This quantitative research uses a descriptive quantitative method, sampling 52 employees working in the Gorontalo Provincial Health Office. The data collection techniques are observation, questionnaires, documentation, and data analysis techniques, such as simple regression using the SPSS version 21.0 program. The results showed that there was a positive and significant influence between the office administration system and employee work efficiency at the Gorontalo Provincial Health Office, this was indicated by the value of tcount > ttable (5.970)>(1.675) and the significant probability value of 0.000 < 0.05. The coefficient of determination (R Square) value of the regression model previously obtained was 0.416, which means that 41.6% of the variability of employee work efficiency can be explained by the Office Administration System applied at the Gorontalo Provincial Health Office, In other words, the better the administration system is implemented, the better its contribution to increasing employee work efficiency. The residual value generated or influenced by other variables not examined in this study was 58.4%.